MODULATION OF FEELS : EXPRESSION OF FEELINGS WITH MUSICAL TONATION AS TRIGGER. - Gita Sakanti, Saskia
Music and drawing are two things that plays a big role in the writer's life, both can function as a form of art that help express feelings that develop in humans. A deeper awareness and understanding of those two things has led to the question of how to interpret the role and correlation between music and drawing in the writer’s current creative process. The construction of non-representative visual forms became the writer's choice during the process of this work, considering feelings as subjective perceptions and not having a definite visual definition. The feelings that the writer raises are the feelings that arise when listening to music, because music is the only thing that can help the writer feel things easily. During the process of creating these artworks, the writer develops a method of her own that’s based on labanotation theory and music patiture that serves as a guide. This method will act as a guide to help the author in imagining the visualization of shapes and help the writer's intuition while creating the drawing. The writer understands that drawing as a medium can manifest very ambiguous feelings in the human mind. In addition, drawing is a spontaneous and intimate process compared to other types of media based on the writer’s personal experience. Thanks to that, the writer can make every line, shape, and color in these artworks an actualization of personal feelings and experiences. Through the exploration of this work, the writer believes that music and drawing have the same role as triggers of intense feelings in the process of self-development for the future.